Low-cost ocean wave energy converter kit as a teaching tool of a new alternative energy source. (13th July 2020) - Satriawan, Muhammad; Liliasari, Liliasari; Setiawan, Wawan; Abdullah, Ade Gafar
Abstract: This research aims to develop an ocean wave energy converter kit from low-cost materials as a teaching tool. The kit is developed using the working principle of a wave energy converter that uses a buoy as a system drive and a weight balancer that is connected to a chain. The dimensions of the kit are 6.7 × 0.3 × 0.4 m (length × width × height) with the ratio of the final wheel used is 1:40. The kit generated electricity when the system was driven by a buoy that utilized vertical wave action. The test kit was carried out in the marine engineering laboratory through three stages each using a wave period of 1 s, 2 s, and 3 s at a wave height of 0.1 m, 0.15 m and 0.20 m. The observed data was the voltage generated by the kit using a digital multimeter. The observed data is the amount of voltage generated by the developed kit, and each observation takes 60 s. Based on observations during the experiment, the kit was functioning properly. The results showed that with a greater wave period, the kit produced smaller voltage, and with a greater wave height, the kit produced greater voltage. We finally found that the voltage generated by the kit was affected by the wave period and wave height.